أثر الملموسية في جودة الخدمات الصحية : دراسة استطلاعية لآراء العاملين في مجموعة مختارة من مستشفيات محفظة نينوى - د. الاء حسيب الجليلي; رياض جميل وهاب (PROSPECTIVE RESEARCHES, 2023)
The research aimes at measuring value of tangibles in presenting high quality health services for customers. Consequently presenting tangible elements will excellently contribute in improving quality of services provided in healthy sector. The research affirms that health institutions must pay a great attention to tangibles if they want to provide good health services because one of the important indicators for good quality for the customers’ is visual indicators. The goal of the research is to measure tangibles contribution degree in the improvement of the quality of health services in the organization under study to determine the disadvantages and to find solutions for them, as will as supporting the advantages. The research hypothesis that "tangibles have sens impact in improving the quality of health in the organizations under study". The sample includes employees from three hospitals in Nineveh. However, data analysis leads to a set of findings; the most prominent is that there is a strong impact for tangibles in the quality of health services. Also, group of recommendations are given; the main one is the necessity of keeping the physical facilities clean, tidy and continually updated in order to improve the quality of health services.